Thai voice language encryption and decryption using 3DES and AES algorithm for communication - Dobay, Naruemon; Thakong, Mongkhon; Somkantha, Krit; Somsuk, Kritsanapong (2025 13th International Electrical Engineering Congress (iEECON), 2025)
The aim of this paper is to compare the performance of the encryption and decryption of Thai voice language by using Triple Data Encryption Standard (3DES) and Advanced Encryption Standard (AES) algorithms for secure communication. The research methodology involves collecting Thai voice samples, converting speech to text by using Google's API to be applied with cryptography algorithms. Performance comparison between 3DES and AES focuses on accuracy and processing time. Experimental results demonstrate 100% accuracy in preserving original text content for both algorithms. However, AES consistently outperforms 3DES in processing speed, particularly for larger data sizes. The study reveals a linear relationship between input size and processing time for both algorithms. Furthermore, the findings imply that AES offers superior performance in terms of speed and security for encrypting Thai voice data, making it more suitable for secure communication applications. Therefore, this research contributes to improve data security in Thai voice communications by providing empirical evidence on the efficacy of modern encryption standards.